1002. A Daily Single Tablet Regimen (STR) of Bictegravir/Emtricitabine/Tenofovir Alafenamide (B/F/TAF) in Virologically-Suppressed Adults Living with HIV and End Stage Renal Disease on Chronic Hemodialysis. (31st December 2020) - Eron, Joseph J; Wilkin, Aimee; Ramgopal, Moti; Osiyemi, Olayemi; McKellar, Mehri; McKellar, Mehri; Slim, Jihad; Asmuth, David; DeJesus, Edwin; German, Polina; Blair, Christiana; Carter, Christoph C; et al.
Abstract: Background: Treatment for people living with HIV (PLWH) and end stage renal disease (ESRD) on hemodialysis (HD) has previously required complex dose-adjusted regimens. We evaluated a daily regimen of elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF) and established this treatment as effective and safe, showing that daily TAF resulted in lower plasma tenofovir exposure than a historical comparison of once weekly tenofovir disoproxil fumarate in patients with ESRD on HD. After week (W) 96, participants transitioned to daily B/F/TAF to assess whether efficacy and safety would be maintained on this STR that is guidelines-recommended for PLWH with eGFR > 30 mL/min. Methods: Virologically suppressed adult PLWH with ESRD on chronic HD who completed W96 on E/C/F/TAF enrolled in the B/F/TAF extension for 48 weeks. Efficacy was assessed as the proportion of participants with virologic suppression (HIV RNA < 50 copies/mL). Safety was assessed throughout the study, PK was assessed using sparse sampling at W4, 24 and 48. Results: 55 enrolled, 36 completed E/C/F/TAF, 10 entered the B/F/TAF extension. The median age was 55 yrs (range 34-63); median time on HD was 4 yrs (range 2-16). All ten participants on B/F/TAF had HIV-1 RNA < 50 c/mL (95% CI 69%, 100%) at W48. All participants had at least 1 adverse event (AE); most were grade 1 or 2 in severity. One participant had a grade 3 AE and 3 had serious AEs; none were considered related to study drug by the investigator. One participant had AEs attributed to study drug (malaise grade 1 and nausea grade 2), which resolved and did not lead to discontinuation of study drug. There were no clinically relevant changes in fasting lipids. In participants with evaluable data (n=2-5 per timepoint), mean bictegravir trough concentrations were lower compared to PLWH not on HD but remained 4- to 7-fold higher than the established protein-adjusted 95% effective concentration (paEC95 ) of 162 ng/mL against wild-type virus. Conclusion: A once daily regimen of B/F/TAF maintained virologic suppression in PLWH on chronic HD. B/F/TAF was well-tolerated with no discontinuations. B/F/TAF may be an effective, safe and convenient once daily STR and ameliorate the need for dose adjustment in appropriate PLWH who require chronic HD. Disclosures: Joseph J. Eron, MD, Gilead Sciences (Consultant, Research Grant or Support)Janssen (Consultant, Research Grant or Support)Merck (Consultant)ViiV Healthcare (Consultant, Research Grant or Support) Aimee Wilkin, MD, MPH, Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member)GlaxoSmithKline (Grant/Research Support)Janssen (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member)Pfizer (Grant/Research Support) Moti Ramgopal, MD FACP FIDSA, AbbVie (Speaker's Bureau)Allergan (Speaker's Bureau)Gilead Sciences Inc. (Consultant, Scientific Research Study Investigator, Speaker's Bureau)Janssen (Speaker's Bureau)Merck (Consultant)Viiv Healthcare (Consultant) Olayemi Osiyemi, M.D, GlaxoSmithKline (Advisor or Review Panel member, Speaker's Bureau)ViiV Healthcare (Advisor or Review Panel member, Speaker's Bureau) Jihad Slim, MD, Abbvie (Speaker's Bureau)Gilead (Speaker's Bureau)Jansen (Speaker's Bureau)Merck (Speaker's Bureau)ViiV (Speaker's Bureau) David Asmuth, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Edwin DeJesus, MD, Gilead Sciences (Advisor or Review Panel member) Polina German, PharmD, Gilead Sciences (Employee) Christiana Blair, MS, Gilead Sciences (Employee, Shareholder) Christoph C. Carter, MD, Gilead Sciences Inc. (Employee, Shareholder) Diana M. Brainard, MD, Gilead Sciences (Employee) Sean E. Collins, MD, MS, Gilead Sciences (Employee) Hal Martin, MD, MPH, Gilead Sciences Inc. (Employee, Shareholder)